Design and simulation of a UHF band radio frequency quadrupole (RFQ) proton accelerator - Çelebi, Emre. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
This thesis introduces DemirciPro, a computer program created to design and simulate low-energy beamlines, along with the UHF band radio frequency quadrupole (RFQ) designed as part of the Proton Testbeam At Kandilli (PTAK) project. The RFQ has undergone trial production and measurements, and this thesis documents its results. DemirciPro is a computer program that is developed within KahveLAB. DemirciPro strives to design low- energy beamlines with a single robust interface. It simulates all the critical elements of a low-current beamline except for the ion source. Moreover, DemirciPro has the potential to govern other design and simulation codes using a single interface, thereby enabling the simulation of the whole beamline using industrystandard programs. In this thesis, we provide a brief overview of the Proton Testbeam At Kandilli (PTAK) project, including the current test results of its components. We then delve into the details of RFQ, including its original RFQ vane-tip design and the novel design approach followed. We also present the findings of the completed trial production over the past years. Lastly, we compare the vane-tip measurements of test production with the design and discuss the effects of production errors on the simulation results.
Keywords: Shortwave radio.; Radio frequency modulation.